Geomagnetic Dipole Changes and Upwelling/Downwelling at the Top of the Earth's Core - Huguet, Ludovic; Amit, Hagay; Alboussière, Thierry (Frontiers in Earth Science, 2018)
The convective state of the top of Earth's outer core is still under debate. Conflicting evidence from seismology and geomagnetism provides arguments for and against a thick stably stratified layer below the core-mantle boundary. Mineral physics and cooling scenarios of the core favor a stratified layer. However, a non-zero secular variation of the total geomagnetic energy on the core-mantle boundary is evidence for the presence of radial motions extending to the top of the core. We compare the secular variation of the total geomagnetic energy with the secular variation of the geomagnetic dipole intensity and tilt. We demonstrate that both the level of cancellations of the sources and sinks of the dipole intensity secular variation, as well as the level of cancellations of the sources and sinks of the dipole tilt secular variation, are either larger than or comparable to the level of cancellations of the sources and sinks of the total geomagnetic energy secular variation on the core-mantle boundary, indicating that the latter is numerically significant hence upwelling/downwelling reach the top of the core. Radial motions below the core-mantle boundary are either evidence for no stratified layer or to its penetration by various dynamical mechanisms, most notably lateral heterogeneity of core-mantle boundary heat flux.